Tragedia Saul Vittorio Alfieriego w adaptacji Wojciecha Bogusławskiego. Rekonesans badawczy - Purgał, Liwia (Tematy i Konteksty, 2016)
The work of Wojciech Bogusławski, adaptation from the tragedy by Vittorio Alfieri, depicts two characters who present their arguments to each other. King Saul is characterized by cruelty and quite pathological pride, whereas David, his adversary, is noble, valiant and ready to sacrifice himself for the good of his country. The events of the tragedy are modelled after the biblical story of King Saul, who is abandoned by the spirit of God, and David, favoured with the blessing of the Creator, presented in the First Book of Samuel. Yet, the tragedy of Alfieri-Bogusławski is not only a rephrased version of the biblical text because the time of the plot begins when the story in the Bible finishes. The biblical events in the tragedy are shown in flashback. The paper is a research reconnaissance, as it presents fundamental remarks on the interpretation of the tragedy and suggestions for further study, especially concerning the function of the characters’ performance. Further examination is needed of the technique used by Bogusławski in adapting the work of Alfieri, and of the translation. The paper only presents general characteristics of the Polish translator’s decisions. Boguławski himself was aware of the consequences of translating a rhyming piece as prose. He strove to write concisely, to salvage the depth of thought and the expressive power of the original, to preserve most of the language, which would enable accurate communication with the reader, delight of the audiences, compassion for the characters, pity, fear, and thus to recreate high style in order to reproduce the category of grandeur, pathos and heroism. From the analysis of selected aspects of Bogusławski’s literary technique and artistry, it appears that the tragedy is an artistically mature piece and should be subject to further, more detailed study.